Preparation and Characterization of Nanocrystalline Hard Chromium Coatings Using Eco-Friendly Trivalent Chromium Bath - V. S. Protsenko; V. O Gordiienko; F. I. Danilov; S. C. Kwon (E-Journal of Chemistry)
A new aqueous sulfate trivalent chromium bath is described. The chromium bath contains formic acid and carbamide as complexing agents. Chromium was deposited at a temperature of 30÷40 oC and a cathode current density of 10÷25 A dm-2. The bath allows obtaining thick (up to several hundred micrometers) hard chromium coatings with nanocrystalline structure. The electrodeposition rate reaches 0.8÷0.9 µm min-1.